Plain Package; Can It Affect Health Awareness and Quit Smoking Attempt Behavior? - Eko Mohammad Fitrianto (Program Studi Magister Manajemen FE Unsri, 2018)
AbstractPurpose: Graphic Pictorial Health Warnings (GPHW) Policy has been implemented in Indonesia since 2014, but the numbers have never shown declining yet. A few countries like Australia and Canada use plain package policy as a new approach to reducing it. Even the plain package policy has been not implemented in Indonesia, this could be preliminary research as an alternative solution.Design/Methodology/Approach: Paired t-test conducted to test the significant difference between smoker’s perception about a regular and plain package. Because of a plain package has not implemented yet, we demonstrate a product’s prototype and ask them to imagine if the policy has actually implemented. This preliminary research use cross-section methods to gain the data. To test the effect, we collected information from 200 active smokers in Palembang, Indonesia using a questionnaire.Findings: Significant difference (< 0.05 ) occurs between smoker's perception about health awareness and quit smoking behavior at the regular and plain package. There is 9 item to compare each other and two overall variables. Six of a nine-item variable has significant difference each other (< 0.05), and also two others (< 0.05).Practical implication: As preliminary findings, this significant difference addressed to formulate a better GPHW Policy. It can use to gain more smoker's attention to health awareness and drive quit smoking attempt behavior. And we propose ongoing social marketing campaign related to amplify the effect of a plain package according to research findings.Originality/value: We conduct a preliminary test to compared smoker’s perception at the regular package and plain package, even the plain ones have been not implemented yet. To make more realistic about plain package’s response, we use a prototype to amplify their visualization. Social marketing campaign related to a plain package ongoing.Keywords: disturbing pictures on cigarettes pack, graphical picture health warning, health awareness, quit smoking attempt behavior, social marketing.